Re-Examining Implementation of Policy on Equity in Education in Malaysia - Nordin, Abu Bakar (EDUCARE, 2012)
ABSTRACT: Democratization of education implied that all children of school age should have the right to be in schools and also have the right to be assisted to achieve as much as what their cohorts have achieved or what has been specified by the curriculum. However, owing to variations in factors such as family economic and education backgrounds, ethnicity, school locations, school and teacher distributions, allocation of school funds, diversity in the implementations of specific reforms, the presence of physically and mentally handicapped students and parent-teacher association involvement in school activity; accessibility and achievement fell short of the expectation. In examining the current forms of policy implementation and reforms discrepancies found run not only counter to the sacred doctrine of democratization of education but also work against the sacred goals of providing equal education opportunity for all children. Streaming according to performance, despite having its own advantages, does not help in either accessibility or achievement and thereby antithetical to equity. Therefore, the current practices in the implementation of the policy and reforms should be re-examined within the context of a reliable framework, so that remedial and much more innovative considerations such as purposeful distributions of teachers, making additional fund available for needy schools, streaming according to the needs of children to be able to learn effectively, and dispensing some allocation and organizational skills to educate parents to be actively involved in school activities can purposefully be undertaken.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â KEY WORDS: Equity in education, education policy in Malaysia, re-examining policy in education, and education and equity.===About the Author: Prof. Dr. Abu Bakar Nordin is an Emeritus Professor at the Faculty of Education UM (University of Malaya), 50603 Kuala Lumpur, Malaysia. For academic purposes, he can be reached via e-mail address at: a_bakarnordin@um.edu.my and a.bakar43@yahoo.comHow to cite this article? Nordin, Abu Bakar. (2012). âRe-Examining Implementation of Policy on Equity in Education in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.51-64. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 21, 2012); Revised (July 23, 2012); and Published (August 17, 2012).